Pengembangan Potensi Wisata Pantai Jai-Jai Raok Oleh Bumdes di Desa Padang Tanggung Kabupaten Kuantan Singingi - Nermoriati Nermoriati; Zulkarnaini Zulkarnaini (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Jai-jai Raok Beach tourist attraction is one of the beach-style tourist destinations consisting of white sand and coconut trees that make this place look like a beach in general. Jai-jai raok beach is located in the village of Padang Responsi, Kuantan Singingi Regency. This study aims to determine how the development of jai-jai raok beach tourism by BUMDes Rajo Bujang. This research uses descriptive qualitative method because it is done by interview, observation, and documentation. The results of the study indicate that the development of this tourism is still quite good, but there are still many shortcomings that must be improved such as facilities and tourism promotion. In addition, there are also inhibiting factors from this development, namely poor fund management and tourism promotion that has not been maximized and also flooding caused by rain so that this beach activity stops.